Pulsation in the white dwarf HE 1017−1352: confirmation of the class of hot DAV stars. (4th June 2020) - Romero, Alejandra D; Antunes Amaral, L; Kepler, S O; Fraga, L; Kurtz, D; Shibahashi, H
ABSTRACT: We report the detection of periodic variations on the T_eff32 000 K DA white dwarf star HE 1017−1352. We obtained time series photometry using the 4.1-m Southern Astrophysical Research telescope on three separate nights for a total of 16.8 h. From the frequency analysis, we found four periods of 605, 556, 508, and 869 s with significant amplitudes above the 1/1000 false alarm probability detection limit. The detected modes are compatible with low harmonic degree g-mode non-radial pulsations with radial order higher than ∼9. This detection confirms the pulsation nature of HE 1017−1352 and thus the existence of the new pulsating class of hot DA white dwarf stars. In addition, we detect a long period of 1.52 h, compatible with a rotation period of DA white dwarf stars.